UPAYA MENINGKATKAN HASIL BELAJAR SISWA DENGAN PEMBERIAN PENDEKATAN HIGH TOUCH DALAM PEMBELAJARAN SENI BUDAYA (MUSIK) DI KELAS VIII 9 SMP NEGERI 13 PADANG - Tiya Efti Saputri; Tulus Handra Kadir; Irdhan Epria Darma Putra (SENDRATASIK UNP, 2017)
This article aims to determine whether by giving high touch aspects in the learning process can improve student learning outcomes. The type of this research is Classroom Action Research (PTK), which aims to improve the learning process to improve student learning outcomes in class VIII 9 SMP Negeri 13 Padang. The object of research in this research is the students of class VIII 9 SMP Negeri 13 Padang. Sources of data in this study is the process and the results of the action is done that is giving high touch aspects on the learning process on the students of class VIII 9 in SMP Negeri 13 Padang. Data collection techniques used were interviews, observation, literature study and documentation. The results showed that the giving of aspects in the process of learning art and culture (music) in class VIII 9 SMP Negeri 13 Padang gave positive results to the students. Student learning outcomes increase as well as students appreciate teachers in the learning process. Unexpected behavior is no longer shown by the student. Keywords: Effort, Learning Outcomes, High Touch, Cultural Art (Music)